2006
DOI: 10.2353/ajpath.2006.050163
|View full text |Cite
|
Sign up to set email alerts
|

p75 Neurotrophin Receptor-Mediated Signaling Promotes Human Hair Follicle Regression (Catagen)

Abstract: Nerve growth factor (NGF) and its apoptosis-promoting low-affinity receptor (p75NTR) regulate murine hair cycling. However, it is unknown whether human hair growth is also controlled through p75NTR, its highaffinity ligand pro-NGF, and/or the growth-promoting high-affinity NGF receptor tyrosine kinase A (TrkA). In microdissected human scalp anagen hair bulbs, mRNA for NGF, pro-NGF, p75NTR, and TrkA was transcribed. Immunohistomorphometry and in situ hybridization detected strong NGF and pro-NGF expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 44 publications
5
49
0
Order By: Relevance
“…As reported previously, 9,11,17,19,23 K15 (bulge marker), CD200 (bulge marker), CD34, and CD271 were strongly and differentially expressed in the outermost layer of the ORS in cells that adhered to the basement membrane ('basal cells'; Figure 1a). Other cytokeratins (K1 and K14) and integrins Figure 1 Biomarker expression profiles in human epidermis and the anagen hair follicle.…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271mentioning
confidence: 58%
See 2 more Smart Citations
“…As reported previously, 9,11,17,19,23 K15 (bulge marker), CD200 (bulge marker), CD34, and CD271 were strongly and differentially expressed in the outermost layer of the ORS in cells that adhered to the basement membrane ('basal cells'; Figure 1a). Other cytokeratins (K1 and K14) and integrins Figure 1 Biomarker expression profiles in human epidermis and the anagen hair follicle.…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271mentioning
confidence: 58%
“…15 In humans, however, anti-CD34 antibodies failed to label the bulge, but instead labeled the proximal (lower) half of the ORS. 16,17 A recent study confirmed that CD271 (p75-neurotropin receptor), known as a marker of neural stem cells or neural crest cells, 18 was also expressed in the human proximal ORS; 19 thus its expression pattern resembled that of CD34.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Hair cycle morphology and development may be regulated by NGF as well as neurotrophins (4,93,94,96,98,620,638). In mice, the p75 neurotrophin receptor has been shown to control apoptosis-driven hair follicle regression.…”
Section: B Ngf and Nt Receptorsmentioning
confidence: 99%
“…HF immune privilege, connective tissue sheath (CTS) mast cell degranulation. (see Arck et al, 2005a; Bodó et al, 2005 and2007; Botchkarev et al, 2004; Colombe et al., 2007; Deplewski and Rosenfield, 2000;Hasse et al, 2007; Kauser et al, 2006;Ohnemus et al, 2006;Paus et al, 2006;Peters et al, 2006b and2007;Philp et al, 2004;Slominski et al, 2007;Telek et al, 2007;Zouboulis et al, 2007) While this remains to be conclusively demonstrated, it is likely that HFeSC are fully integrated into this neuroendocrine tapestry of general HF biology. However, all we have to go by currently are some pointers to potentially important elements in the as yet obscure neuroendocrinology of HFeSC.…”
mentioning
confidence: 99%